Advanced recording schemes for electron tomography. (7th July 2016) - Dahmen, Tim; Trampert, Patrick; de Jonge, Niels; Slusallek, Philipp
Abstract: Abstract : Three-dimensional (3D) scanning transmission electron microscopy (STEM) has become one of the primary tools for analytical characterization in materials science and also finds increasing use in the life sciences. A number of different recording schemes exist for the acquisition of 3D data using STEM, each capturing different spatial frequencies and, thus, different information about the shape of a specimen. In this article, we present and compare different sampling approaches based on images with both large and small depth of field. We highlight the latest contribution to 3D data acquisition, the combined tilt, and focal series. This recording scheme combines the advantages of tilt series-based tomography with 3D data acquisition using a focal series and is particularly beneficial for imaging specimens with a thickness of 1 µm or greater.